DRIVING TRANSPARENCY : THE ROLE OF GOOD CORPORATE GOVERNANCE AND LEVERAGE SHAPING SUSTAINABILITY REPORTING, WITH PROFITABILITY AS A MODERATOR - Almatin, Nurlaeli Risna; Simatupang, Frido Saritua (Indonesian Journal of Strategic Management, 2025)
Disclosure of sustainability reports has experienced significant development and is now an important element for every organization. This research contributes to deepening understanding of the influence of Good Corporate Governance (GCG) and leverage on sustainability report disclosure, with profitability as a moderating variable in companies listed on the LQ45 index of the Indonesia Stock Exchange in the 2021-2023 period. Using a quantitative approach with descriptive and associative methods, this research relies on data obtained from annual financial reports and sustainability reports of companies listed on the Indonesia Stock Exchange. The research sample consists of 28 companies which are part of the population of 62 LQ45 companies during the period studied. The main findings of this research are: 1) institutional ownership has a positive influence on sustainability report disclosure, 2) independent board of commissioners does not show a significant influence on sustainability report disclosure, 3) debt to asset ratio has a negative effect on sustainability report disclosure, and 4) return on assets cannot moderate the relationship between institutional ownership, independent board of commissioners, and debt to asset ratio with sustainability report disclosure. It is hoped that these findings can become a useful reference for stakeholders, including companies and regulators, in increasing the transparency and accountability of sustainability reports, as well as encouraging a more effective application of GCG principles in the business world.